Metode Simaan dan Murajaah dalam Menghafal Al-Quran di Pondok Pesantren Nurul Quran Patokan, Kraksaan, Probolinggo - Hasanah, Imroatul; Khumaidi, Ahmad; Maghfiroh, Ummi Lailia (STAI Auliaurrasyidin Tembilahan, 2023)
In the current era, several methods have emerged in the process of memorizing the Koran, but the implementation of the Sima'an and Muraja'ah methods has persisted to this day, especially at the Nurul Quran Kraksaan Islamic boarding school. The aim of this research is to find out the implementation of the simaan and murajaah methods at the Nurul Quran Patokan Islamic Boarding School, Kraksaan Probolinggo. The qualitative approach was chosen by collecting data through observation. The results of the study show that there are supporting and inhibiting factors in memorizing the Al-Quran. The supporting factors are enthusiasm in memorizing the Koran properly and correctly, increasing and being able to reach the target. While the inhibiting factor is prioritizing simaan, namely wanting to memorize a lot but putting aside murojaah. So, it is not uncommon for many students to memorize verse by verse but are not fluent in the previous verses.